2012
DOI: 10.1109/titb.2012.2201950
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Kinematic Changes With Fatigue in Running Using Body-Worn Sensors

Abstract: In this paper, we investigate monitoring of kinematic changes evoked by fatigue in running using wearable technology. Movement data were recorded with ETHOS devices. ETHOS is the ETH Orientation Sensor, a customized inertial measurement unit for unconstrained monitoring of human movement. We perform two real-world experiments, in which 21 runners of different skill levels participated. The real-world experiments capture two exhausting 45-min runs: one on a treadmill and one on a conventional outdoor track. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
132
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(135 citation statements)
references
References 18 publications
1
132
0
2
Order By: Relevance
“…Le Bris et al 31 investigated the effect of fatigue on middle distance runner's stride patterns using the Locometrix system (Locometrix™, Centaure Metrix, France) located on the lower back. While they looked at stride regularity (similarity of cranial-caudal acceleration over successive strides) and stride symmetry (similarity of cranial-caudal acceleration over left and right strides) through autocorrelation, these variables are similar to those found by papers looking at vertical acceleration 5,10,14,22,23,32 .…”
Section: Remaining Parametersmentioning
confidence: 69%
See 3 more Smart Citations
“…Le Bris et al 31 investigated the effect of fatigue on middle distance runner's stride patterns using the Locometrix system (Locometrix™, Centaure Metrix, France) located on the lower back. While they looked at stride regularity (similarity of cranial-caudal acceleration over successive strides) and stride symmetry (similarity of cranial-caudal acceleration over left and right strides) through autocorrelation, these variables are similar to those found by papers looking at vertical acceleration 5,10,14,22,23,32 .…”
Section: Remaining Parametersmentioning
confidence: 69%
“…By using the above methods previous research has identified symmetry in running gait 5 , examined the validity of accelerometers in assessing vertical parameters 5,10,14 and shown that there is little difference between vertical acceleration in anatomical and prosthetic strides 32 . Previous studies have also found conflicting results as to levels of vertical oscillation, dependent on running ability 22,23 .…”
Section: Shock Attenuationmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, these sensors offer the advantages of collecting multiple consecutive gait cycles and eliminate the issue of targeting. Numerous authors have already used MEMS to detect FS in a variety of conditions [8,[14][15][16][17][18][19][20]. Nevertheless, just one study was found which investigated the accuracy of MEMS for detecting FS during running by comparing those data to a synchronized force plate signal [21].…”
Section: Introductionmentioning
confidence: 99%